Gingival Pigmentation Pattern in Correlation to Skin Color in a Group of Kurdish People in Sulaimani City - Amin, Soma; Azeez, Shokhan H. (AL-Kindy College Medical Journal, 2022)
Background: Melanin pigmentation of the gingiva appears in all ethnicities. Excessive pigmentation is an esthetic concern that has increased awareness about depigmentation procedures. This epidemiological study aims to find the correlation between skin color and gingival pigmentation in Sulaimani Governorate, Kurdistan/Iraq.Subjects and Methods: A total of 820 apparently healthy and non-smokers, including 338 males and 482 females with healthy gingiva, aged between (18-40 years old) were enrolled in this study. Clinical examination on the participants’ gingivae was performed to assess color, and the distribution of pigmentations. Afterward the of participants skin color were visually examined and divided into six groups according to the Fitzpatrick scale.Results: Skin color of (53%) of our participants was medium to light brown. Most of the pigmentations were observed in the attached gingiva and interdental papilla (26.83%) and least being in the marginal gingiva and interdental papilla (9.27%). A statistically significant correlation was found between the participants’ skin color, and the intensity of their gingival pigmentations  Conclusion: Darker-skinned subjects haveeavieringival pigmentation compared toair-skinned people in Sulaimani Governorate, Kurdistan/ Iraq. The intensity of gingival pigmentation increases with age with the highest rate of gingival pigmentation was in the upper and lower second premolar to premolar area.